Characterization of Geographically Isolated Stocks of Lamellidens marginalis (Lamarck, 1819) Using Microsatellite Markers - Nahida Quyoom; Shubham Varshney; Sonal Suman; Aparna Chaudhari; P. Gireesh-Babu; Rekha Das; Pradeep A; Annam Pavan Kumar (Journal of Indian Fisheries Association, 2024)
The Indian freshwater mussel, Lamellidens marginalis, is one of the key candidate species for pearl production in India. The conservation status of L. marginalis has been assessed as ’least concern’, and the population trend of the species is not known. However, the increased anthropogenic activities such as overexploitation, release of industrial or agricultural waste, and construction of dams are posing threats to the natural stocks. For sustainable management of resources, knowledge of genetic stock structure is essential. Further, the genetic variation between the genetic stocks could manifest in the form of pearl quality. We analyzed the genetic structures of five populations collected from Tripura (2 locations), Maharashtra, Gujarat, and Odisha using three microsatellite (di-nucleotide SSR: 2; trinucleotide: 1) markers. Locus-wise, the number of alleles varied from 2 to 4, with an average of 2 alleles per locus. The mean observed and expected heterozygosity values varied from 0.253 to 0.345 and 0.459 to 0.638, respectively. All the stocks were in Hardy–Weinberg equilibrium, and no null alleles were observed. Pairwise FST analyses showed moderate genetic differentiation among the stocks of Maharashtra, Odisha, and Gujarat. The loci showed moderate diversity within the stocks and revealed moderate to high genetic differentiation among the stocks.